“Close Enough to One Another and Far Apart as Well”: The Intersection of Literature and History in Seamus Deane’s Reading in the Dark - Poiana, Fernando Aparecido (ABEI Journal, 2013)
This article analyses the intersection of narrative and history in SeamusDeane’s Reading in the Dark (1996). It uses the Benjaminian notions of memory, narration and experience to investigate how this novel creates a self through a language characterized by the absence of what it refers to. The analysis will eventually demonstrate that the tension between recollection and obliteration makes Literature and History converge as products of a narrative act.Keywords: Seamus Deane; Reading in the Dark; literature and history.